Psychosocial Well-being of Children and Adolescents in Latin America : Evidence-based Interventions - Sarriera, Jorge Castellá; Bedin, Lívia Maria (Springer International Publishing : Imprint: Springer, 2017)
This book discusses child well-being, with children and adolescents as key informants, from a Latin American perspective. It explores theoretical and empirical issues related to well-being and associated aspects, in order to understand the well-being of this population. Topics analyzed in this volume address for instance environment and community, rights, leisure time, technologies, interpersonal relationships and spirituality and their implications for changes in the well-being in children and adolescents. Especially relevant for scholars and professionals in the social and health sciences, as well as policy makers, seeking to promote child well-being, regardless of the area in which they operate.
Keywords: Social sciences.; Medical research.; Quality of life.; Well-being.; Children.; Developmental psychology.; Positive psychology.; elektronické knihy; electronic books